The Lesson of literature and ICT. The Mentimeter Application - Mihaela Stanciu (Revista de Pedagogie, 2019)
Progressively, the differences between generations can be observed in schools, not only from the mentality point of view, but also through the evolution of technology. Nowadays, school has to adapt to the society’s development rhythm and prepare the youth for the future, which is characterized by change, advanced technology and science. As a Romanian Literature and Language teacher, the question which is raised is in what way the strategies, methods, and means used in class can be updated to the new types of communication and the necessities that students have according to the fundamental change of the society, such that the connection teacher-student can be realised in a more constructive and motivational way. This article proposes a new way of reflection for teachers interested in the optimization of methods and teaching means used in class – Mentimeter represents an innovative element in Romania, but currently used in the United Kingdom for high-school classes and university lectures. We will take into consideration how to define this concept, the process, the necessary means and materials, the lesson category, how to give suitable tasks in order to highlight the teacher’s and student’s role, realising didactic applications. In our opinion, Mentimeter can be an ICT method used in education, but it’s success depends on the teachers’ creativity and open-mindedness to innovation.